(untitled) - Hughes, Glyn S. (Oxford, 1998)
The book is divided into 10 units, the first two units concentrating on giving instructions and asking questions. Units 3 - 10 cover a wide variety of situations with occur in the classroom such as arranging work, preparing for a task, using audio-visual aids, and checking understanding. Each unit is followed by a thorough series of exercises (with a Key).
Keywords: English language; Study and teaching,Foreign speakers